SISTEM PENGAMBILAN KEPUTUSAN UNTUK REKOMENDASI PEMBELIAN PRODUK DENGAN MENGGUNAKAN METODE FUZZY MCDM (Studi Kasus PT. Nerangi Sarana Karya) - Iddo Elianta Herlambang Iddo Elianta Herlambang (LPPM Universitas Sains dan Teknologi Komputer, 2022)
Decision support systems are interactive computer-based systems that help decision makers to use data and models to solve unstructured problems. Decision support systems (DSS) combine the intellectual resources of individuals with computer capabilities to improve decision quality. Nerangi Sarana Karya is a company engaged in the engineering sector, in its daily activities PT. Nerangi Sarana Karya carries out production activities, in support of production activities it requires a lot of tools in the form of tools, if these tools run out it will hamper production activities, the purchasing department is responsible if the tools run out, in this implementation the purchasing part is difficult determine the decision to purchase the product because the tools needed have a large number, different sizes and many more criteria. This system functions to recommend product purchases by analyzing or calculating several products with several criteria so that they can be ranked in order from top to bottom, the top one has the highest calculation that can be recommended..